THE PRESENCE OF PENALTY CLAUSE UNDER EMPLOYMENT AGREEMENT - Hernawan, Ari (TANJUNGPURA LAW JOURNAL, 2018)
The research has the objectives of identifying and analyzing the presence of penalty clause under Employment Agreement from Employment Law perspective and identifyng as well as analyzing the implementation of penalty clause under Employment Law by Mediator on Employment within their recommendation.This is a normative and empirical research. The data is obtained from library and field research by way of document review and interview of the subject of research. The data are analyzed qualitatively while the result is presented descriptively. The result research shows that the presence of penalty clause under Employment Agreement is not regulated explicitly under Employment Law, but since one of the aspects of Employment Law is subject to Civil Law through Employment Law, the provision of Contract Law regulated under Book III of The Indonesian Civil Code remains applicable. In this regard, Civil Law must be deemed as law in general, unless otherwise determined by Employment Law. A mediator’s recommendation on Employment Law does not fully implement penalty clause which is presence in The Employment Agreement since it is considered as contradictory to the reasonableness and justice. Mediator prioritizes good faith principle over pacta sunt servanda principle in providing their recommendation.